Characterization of blanching water from the potato processing industry and the influence of processing conditions. (15th February 2023) - Sayed, Akram; Chys, Michael; Sampers, Imca
Abstract: The move towards a circular economy pushes (Belgian) potato processing companies to direct water reuse in high water-consuming processing steps such as blanching. To design a robust treatment for this stream, it is important to know the composition and variability through different seasons, companies and processing conditions. An extensive physicochemical and (limited) microbial characterization was done on samples taken from four different blancher types at seven companies for 1.5 years. High concentrations of organic matter, represented as chemical oxygen demand (9032 ± 4349 mg O2 /L), glucose (0.26 ± 0.32 g/L) or starch (1.40 ± 1.22 g/L) and dissolved ions (348 ± 142 mg Cl − /L and 1279 ± 510 mg potassium/L) were found, at constant ranges independently of the season. This is probably due to the occurrence of a steady state over time for the physicochemical parameters in the water. Concentrations at this steady state or equilibrium could change depending on the used potatoes-to-water ratio used at the blanchers, which is specific to the company and blancher and hence influences the aforementioned equilibrium. From this study, the blanching water shows a high potential for reuse with the (potential) recuperation of thermal energy and by-products. In the case of membrane filtration as a treatment method (ultrafiltration and/or reverse osmosis), the implementation of a pre-treatment to eliminate an excess of solids is recommended together with a possible disinfection or heat exchanger as post-treatment. Highlights: Potato blanching water is highly saturated with organic matter and dissolved ions. The physicochemical composition of blanching water is constant over all seasons. Mainly the potato-to-water ratio affects the blanching waters' organic load. A steady state level of the blanching water is expected to occur after 24–48 h. Potato blanching water has a large potential for water, heat and by-products reuse.